PENGARUH KREDIBILITAS KONTEN BERITA REELS BERBASIS ARTIFICIAL INTELLIGENCE PADA AKUN INSTAGRAM @TVONE.AI TERHADAP TINGKAT KEPERCAYAAN FOLLOWER GEN-Z DI JAKARTA - Irfan Agus Suryana; Dipo Krishyudi Ono; Intan Tri Kusumaningtias (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the influence of content credibility—specifically regarding AI-generated news content on the @tvone.ai Instagram Reels account—on the trust levels of Gen-Z followers in Jakarta. A quantitative approach utilizing a causal research design was employed. The study population consisted of all 24,500 @tvone.ai followers, with a sample of 100 respondents selected via purposive sampling based on the Taro Yamane formula. Data were collected using an online questionnaire featuring a 1–4 Likert scale. Results indicate that both content credibility (mean: 2.93) and trust levels (mean: 3.05) fall into the high category. The t-test yielded a calculated t-value of 15.275 (sig. <0.001), demonstrating a significant influence. The coefficient of determination (R² = 0.704) reveals that content credibility contributes 70.4% to the outcome, while the remaining 29.6% is influenced by other factors. This study confirms content credibility as a primary factor in building audience trust regarding AI-based news content on social media, while reinforcing the relevance of Network Society Theory and the concept of content credibility within contemporary digital communication.